Numerical simulation of hydrodynamic and cavitation performance of pumpjet propulsor with different tip clearances in oblique flow. (1st August 2020) - Qiu, Chengcheng; Huang, Qiaogao; Pan, Guang; Shi, Yao; Dong, Xinguo
Abstract: This work mainly analyzes the variation laws of exciting force, pulsating pressure, velocity distribution and hydrodynamic parameters of PJP at different tip clearances ( δ =0.5 mm, δ  = 1 mm, δ  = 2 mm) and different oblique flow angle (0°, 10°, 20°). In this study, the turbulence model SST k - ω and Reynolds-Stokes equations (RANSE) method have been adopted. The fully structured grid and full channel model have been adopted. And the grid independence of three different tip clearances was verified. In this study, the variation laws of exciting force, pressure coefficient and the hydrodynamic coefficients differences have been studied at the different tip clearances and different oblique flow angle. And the time-domain data of the pulsating pressure of PJP with cavitation conditions or without cavitation conditions was presented, and then which was converted to frequency domain data by fast Fourier transform (FFT). The results show that the torque balance performance of the PJP is broken in oblique flow. The tip clearances have a little effect than the oblique flow angle. The maximum efficiency loss is 19.17% at high oblique angle. The bearing force had a certain phase difference in different tip clearance, the phase shift to the right as the tip clearances increases. At the small advance J  = 1.18, the efficiency with cavitation is greater than non-cavitation condition in oblique flow. In addition, the velocity distribution and the water vapor phase volume fraction of rotor outlet in different oblique flow angles and different tip clearances have been investigated. Highlights: The variation laws of bearing force, pressure coefficient and the hydrodynamic coefficients have been represented at different oblique angle and different tip clearances. Give the comparison of the pulsating pressure and hydrodynamic coefficients differences with non-cavitation or cavitation condition. The water vapor phase volume fraction at different conditions were discussed.